2012
DOI: 10.2147/ijwh.s35280
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of hook wire localization biopsy under imaging guidance for nonpalpable breast lesions detected radiologically

Abstract: BackgroundThe purpose of this study was to evaluate the usefulness of hook wire localization biopsy under imaging guidance for nonpalpable breast lesions detected radiologically.MethodsThis was a descriptive study conducted at the Department of Radiology, Aga Khan University Hospital, Karachi. All patients undergoing needle localization biopsy of a nonpalpable breast lesion under mammographic or ultrasound guidance between January 2009 to December 2010 were included in the study. Patients with incomplete medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…It has been reported that the hook-wire positioning technique has multiple complications, particularly unhooking. Unhooking frequently occurs during patient transfer or during surgery, and may occur under the state of pulmonary collapse or during excision because the operator often strains the positioning steel wire when excising lumps (Tsushima et al, 2008;Masroor et al, 2012). In addition, partial reports have indicated that the cutting closer may cut off the steel wire during surgery (Rozen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the hook-wire positioning technique has multiple complications, particularly unhooking. Unhooking frequently occurs during patient transfer or during surgery, and may occur under the state of pulmonary collapse or during excision because the operator often strains the positioning steel wire when excising lumps (Tsushima et al, 2008;Masroor et al, 2012). In addition, partial reports have indicated that the cutting closer may cut off the steel wire during surgery (Rozen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that as high as 50-80% of biopsies of non-palpable lesions revealed benign results might raise the question that unnecessary biopsies have been performed (5,(24)(25)(26)(27)(28)35). Taking this situation into consideration, from a cosmetic point of view, the decision for surgical excisional biopsy may start to be questioned.…”
Section: Discussionmentioning
confidence: 99%
“…Method of localization is widely variable among literature. Masroor et al [10] had done WGL under mammography guidance in 53% of cases and under ultrasound guidance in 40% of the cases. On the other hand, de Roos et al [11] had in their study ultrasound guided localization in 72.6% of patients, mammography guided localization in 26.5%, and MRI guided localization in 0.9% of patients.…”
Section: Discussionmentioning
confidence: 99%